The influence of integrase inhibitors on weight gain and obesity - a systematic review - Bárbara Barbosa Gonçalves (2021)
Background: Prevalence of obesity is increasing worldwide and it can be triggered by numerous factors, one of them being drugs. Recently studies have begun to emerge describing a possible association between the increasing numbers of overweight and obesity in HIV-infected patients treated with integrase inhibitors. The aim of this systematic review is to gather information about obesity and integrase inhibitors in HIV-infected patients. Methods: A literature search was conducted in MEDLINE, Scopus, Web of Science and in thematic journals. A total of 588 studies published after 2007 about obesity, weight gain, fat, adipose tissue and integrase inhibitors were screened. After removing 336 duplicated articles and excluding 176 according to the exclusion criteria, 76 were eligible for assessing the full text. In the end, 24 studies were included in this review, involving 22000 participants. Results: The male:female ratio was 2.63:1. Weight gain and body mass index (BMI) increase were reported across all studies. Using non-specified integrase inhibitor, the weight increase fluctuated between 0.98 to 5.9 kg and BMI from 0.3 to 0.9 kg/m2, with follow up times spanning from 7 months to 5 years. Using dolutegravir, the follow up time varied between 12 months and 144 weeks with patients gaining up to 7.2 kg and BMI increasing from 0.4 to 2 kg/m2. Regarding raltegravir weight increase diverse from 0.2 to 5.8 kg and BMI from 0.1 to 1.5 kg/m2, during 24 weeks to 44.4 months. When elvitegravir was used, participants were followed between 48 weeks and 2 years with a wide range of weight increase, from 0.5 to 4.1 kg, and BMI, from 0.7 to 0.77 kg/m2. Bictegravir was only used in one study that reported 4.1 kg of weight gain in 144 weeks. Risk factors such as being female, african-american, having lower BMI at baseline, older age and prior treatments for HIV before switching to integrase inhibitors are associated with weigh and BMI increase. Conclusion: All integrase inhibitors can cause weight and BMI gain in HIV-infected patients.